INTENSIVE PRACTICE AND LANGUAGE LABS - Safarova Dildora; Ruzmanova Muxlisa; Abdullaxo’jayeva Feruzabonu; Usmonova Nilufar (TADQIQOTLAR, 2025)
This  article  explores  the  crucial  role  of  intensive  practice  and  language laboratories  in  developing  language  skills.  With  the  advancement  of  technology, language labs have become an essential tool in foreign language instruction, offering immersive,  interactive,  and  self-paced  learning  environments.  Intensive  practice, combined with audio-visual materials, fosters listening, speaking, and comprehension. The article also emphasizes the integration of language labs in educational settings to enhance  learners’  fluency,  motivation,  and  autonomy.  It  is  particularly  useful  for language  teachers,  curriculum  developers,  and  policymakers  aiming  to  implement modern strategies in language education.